Enhancement of the Product Information Collaboration and Access in the Aerospace Industry - Shehab, Essam; Fowler, C.; Rodriguez, Gil A.; Abdalla, Hassan S.; Darwish, Mohamed; Abdulhafed, H.; Ahmed, A.; Ahouie, H.; Alechnovic, A.; Paumes, C.; Tacchini, E.; Urbane, I. (Taylor & Francis, 2013)
This paper presents the development of four scenarios to design a pull mode industrial solution that enables tier-one suppliers to securely and efficiently retrieve data for manufacturing purposes from Original Equipment Manufacturers (OEMs). The research aim is to facilitate and enhance product information sharing between OEMs and their Tier-one suppliers. The proposed Scenarios were developed using PDMLink, which is a Product Lifecycle management system (PLM) and Microsoft SharePoint collaboration platform. The research methodology comprises seven phases including definition of scope, understanding the AS-IS processes, gap analysis, development of the scenarios, and finally validation and cost analysis. This methodology was implemented to select the most suitable scenario for utilising the tools available in the PLM system to accomplish the pull mode data collaboration solution. Data were collected through various ways including semi-structured interviews, workshops with experts, and review of technical documentation on current process. The major benefits of the developed solution are cost reduction due to diminution of resources required for the new process, lead time to access data by suppliers and improved data management. These will reduce the product development cycle, and ensure improved quality of manufactured components.
Keywords: Product Development, Data Sharing, Collaboration, Risk Sharing Partners.